Effect Of Preheating On The Hardness And Microstructure In Shielded Metal Arc Weldments Of A283 B - Ali Akbar (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study was to determine the effect of heating on the welding process of SMAW (Shielded Metal Arc Welding) in terms of hardness and microstructure of welded metal. Much welding has been done by preheating but below the temperature used below the initial martensitic temperature which reaches 452 ° C, this data is sourced from research by S.Zheng et.al and Y. Huang et.al. For this reason, an experiment was carried out with heat temperatures above a martensitic temperature of 500 ° C. The results show that in the Weld Metal area the pearlite structure appears larger, the effect of current strength on HAZ width is directly proportional, the greater the current strength, the wider HAZ, and hardness are affected by the rough grains of martensite